The Influence of NPM, ROA, and EPS on Stock Prices in Food and Beverage Firms - Restuningsih, Jumi; Hertina, Dede (Almana : Jurnal Manajemen dan Bisnis, 2025)
The fluctuation of stock prices in the food and beverage sector reflects investor responses to various financial performance indicators. This study aims to analyze the influence of Net Profit Margin (NPM), Return on Assets (ROA), and Earnings Per Share (EPS) on stock prices in 19 food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Using a descriptive-verificative approach, the research employs multiple linear regression analysis based on secondary data from audited financial statements. The findings reveal that NPM has a significant negative effect on stock prices, indicating that higher margins do not always attract investor interest. ROA, although positively associated, does not have a statistically significant effect. In contrast, EPS has a significant positive impact, suggesting it is a key factor influencing investor decisions. Simultaneously, NPM, ROA, and EPS together significantly affect stock prices. These results underscore the importance of EPS as a reliable performance measure, while also suggesting that other qualitative or external factors may moderate the relationship between profitability ratios and market valuation. This research provides practical insights for investors, financial analysts, and company management in evaluating and responding to firm performance indicators.